Identification of the S100 fused-type protein hornerin as a regulator of tumor vascularity - Michael F. Gutknecht (Nature Portfolio, 2017)
Angiogenesis is essential for solid tumor progression. Here, the authors interrogate the proteome of pancreatic cancer endothelium via phage display and identify hornerin as a critical protein whose expression is essential to maintain the pancreatic cancer vasculature through a VEGF-independent mechanism.